AB0262 SERUM CALPROTECTIN AS A MARKER OF DISEASE ACTIVITY IN PATIENTS WITH RHEUMATOID ARTHRITIS, AXIAL SPONDYLOARTHRITIS AND PSORIATIC ARTHRITIS. (June 2019) - Jarlborg, Matthias; Courvoisier, Delphine; Lamacchia, Céline; Martinez-Prat, Laura; Bentow, Chelsea; Mahler, Michael; Finckh, Axel; Gabay, Cem; Nissen, Michael
Abstract : Background: Calprotectin is a heterodimeric complex of S100A8 and S100A9 calcium-binding proteins. Stored in the cytosol of granulocytes, it is released under cell stress and acts as an endogenous damage-associated pattern molecule. In contrast to C-reactive protein (CRP), it is not an acute phase protein. Serum calprotectin levels correlate with disease activity of several inflammatory rheumatic diseases. Objectives: To investigate association of serum calprotectin with clinical activity in rheumatoid arthritis (RA), axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA). Methods: We performed retrospective analysis of patients with RA, axSpA and PsA from the Swiss Clinical Quality Management (SCQM) registry. Age- and sex-matched asymptomatic first-degree relatives of RA patient without sign of autoimmunity were used as healthy controls (HC, n=72). Serum calprotectin was measured by ELISA (Inova Diagnostics, research use only). Calprotectin levels were categorized into quartiles for each disease. Clinical outcomes included swollen joint count (SJC), CDAI, HAQ and ultrasound power Doppler (USPD) score for RA patients; BASDAI, BASFI and ASDAS for axSpA; SJC and DAPSA for PsA. Comparison of outcomes by calprotectin quartile levels was performed using Kruskal-Wallis tests for continuous outcomes or trend tests for categorical. We used multivariable regression models to compare association of CRP and calprotectin with USPD. Proportions of explained variances were estimated using R 2 . Results: 1729 subjects [RA=969, axSpA=451, PsA=237 and HC=72] were included. 209 RA patients had an ultrasound performed at time of blood collection. Median levels of serum calprotectin were higher in each disease compared to HC ( p <0.01; Figure). In RA, all clinical scores were statistically different across quartiles indicating an association between calprotectin levels and higher disease activity (SJC, CDAI) and severity (HAQ) (Table). In univariable regression models, both CRP (R 2 =0.02, p =0.04) and calprotectin (R 2 =0.10, p <0.001) were associated with USPD scores. Multivariable model analysis revealed that calprotectin alone was as predictive of USPD scores as calprotectin and CRP together (likelihood ratio test between models p =0.14). In axSpA, an association between level of calprotectin and ASDAS score ( p <0.01) was observed. For PsA, SJC, DAPSA and CRP did not differ across calprotectin quartiles. Conclusion: This large study supports the association of serum calprotectin levels with disease activity and severity in RA and shows an association between serum calprotectin and ASDAS in axSpA. Disclosure of Interests: Matthias Jarlborg: None declared, Delphine Courvoisier Grant/research support from: has received an unrestricted grant from MSD for this study, Consultant for: has received consulting fees from BMS, Pfizer, AB2 Bio and Janssen., Paid instructor for: Janssen, Céline Lamacchia: None declared, Laura Martinez-Prat Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Chelsea Bentow Employee of: INOVA Diagnostics, Michael Mahler Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Axel Finckh Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, A2Bio, Bristol-Myers Squibb, MSD, Roche, Pfizer Inc, and UCB, Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm, Michael Nissen Consultant for: AbbVie, Lilly, Novartis, and Pfizer